Personal identity and literature - Hogan, Patrick Colm 1957- (Routledge, Taylor & Francis Group, 2019)
Foreword: Shame -- Introduction: Know thyself -- Basic principles -- Kinds of self -- Becoming oneself: society and identity -- Understanding ourselves: on empathy -- Shame, guilt, and trauma -- Subjectivity and loneliness -- Afterword: a question of dignity